Analysis of the Effect of Calcination Time on Microstructure, Functional Groups, and Crystal Structure of LiNiO2 Battery Cathode Material - Budiarto Budiarto; Edward Baringin Oloan Sihite; Medyawanti Pane (VANOS Journal of Mechanical Engineering Education, 2022)
Battery cathode material is one of the four determinants of energy storage capacity, which is used as a power source in electronic equipment. laptops, and electric vehicles. Synthesis of the cathode material for LiNiO2 battery with one stage co-precipitation method, and variations in calcination time of 3, 6, 9 and 24 hours with a constant temperature of 7000C. Microstructure observations with SEM showed an uneven and homogeneous surface. The elemental compositions of Li, and Ni were analyzed by EDXS showing that Li and Ni metal decreased with increasing calcination time. The results of the crystal structure test using an X-ray diffractometer showed that with increasing calcination time the crystallite diameter decreased, but the dislocation density increased. The micro-lattice strain increased with increasing calcination time in the planes of the Miller hkl index (102), (104), (210), (108), and (113). The FTIR spectra show that the peak at wavenumber 433 cm-1 is caused by the asymmetric stretching vibration of Li–O in LiO6 and bending vibration of NiO6, namely [(Ni–O–Li)], appearing at 603 cm-1.